Cost of illness of breast cancer in Indonesia in 2024: an analysis from the payer perspective - Sudewi Mukaromah Khoirunnisa; Didik Setiawan (Pharmacy Reports, 2026)
Breast cancer imposes a substantial clinical and economic burden in Indonesia, particularly within the National Health Insurance system administered by BPJS Kesehatan. Understanding cost variation by disease severity and care type is therefore essential for efficient resource allocation. This retrospective observational study used BPJS Kesehatan claims data to estimate annual direct medical costs from the payer perspective, categorizing expenses into chemotherapy, radiotherapy, surgery, diagnostic procedures, and follow-up examinations. Costs were analyzed by outpatient versus inpatient care and inpatient severity levels (mild, moderate, severe). The total annual direct medical cost reached IDR 834.11 billion. Outpatient care accounted for the largest share of total expenditure, while inpatient care incurred substantially higher per-patient costs. Costs increased consistently with severity across all components, with chemotherapy, surgery, and radiotherapy identified as the main cost drivers, particularly in severe inpatient cases. Median cost differences between outpatient care and all inpatient severity levels were statistically significant (p<0.001). These findings highlight the significant financial burden of breast cancer on Indonesia’s national health insurance system, strongly influenced by disease severity and inpatient utilization, and underscore the importance of early detection and optimized outpatient care to improve efficiency and long-term sustainability of cancer care financing under Indonesia’s national health insurance system (JKN).